International migration from and to Prussia: 1862-1871 - Thomas K. Bauer; Kathrin Schulze (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Migration has always been an omnipresent topic in Germany. However, unlike today, in the 19th century the German territory was a country of emigration, not immigration. Using county-level data for the period from 1861 to 1871, this paper examines the determinants of emigration from and immigration to Prussia. The empirical results indicate that emigration from Prussia was positively associated with increasing land ownership inequality, urbanization, available transport infrastructure and previous emigration experience, and negatively related to the distance to the nearest port. Average land ownership had an inverted U-shaped effect on emigration. Immigration was concentrated in counties with a high degree of urbanization and a high proportion of industrial workers.) – – Migration ist in Deutschland seit langem ein bedeutendes Thema. Doch anders als heute war Deutschland im 19. Jahrhundert ein Auswanderungsland. Auf Basis von Daten auf Kreisebene für den Zeitraum von 1861 bis 1871 untersucht dieser Beitrag die Determinanten der Auswanderung aus und der Einwanderung nach Preußen. Die empirischen Ergebnisse zeigen, dass die Auswanderung aus Preußen mit der Ungleichheit in der Verteilung des Grundbesitzes, Verstädterung, verfügbaren Verkehrsinfrastruktur und der Auswanderungserfahrung eines Kreises positiv und mit der Distanz zum nächstgelegenen Hafen negativ korreliert ist. Der durchschnittliche Landbesitz hatte einen umgekehrt U-förmigen Effekt auf die Auswanderung. Die Einwanderung nach Preußen konzentrierte sich auf Bezirke mit einem hohen Urbanisierungsgrad und einem hohen Anteil an Industriearbeitern.
Keywords: J15; K37; N33; N9; R23; 330; Age of mass migration; historical migration; determinants of migration; Prussia